Primary Realignment of Posterior Urethral Rupture - Salehipour, Mehdi; Khezri, Abdolaziz; Askari, Rashid; Masoudi, Parham (Urology Journal, 2009)
Introduction: We report the results of treatment of posterior urethral rupture (PUR) by primary realignment with some modifications of the technique. Materials and Methods: In this prospective study, 25 patients (mean age, 33.5 years; range, 18 to 70 years) in whom PUR had been proved underwent primary urethral realignment. All patients were evaluated postoperatively for urinary incontinence, erectile dysfunction, and urethral stricture. They were followed for a mean of 20 months (range, 9 to 27 months). Results: In 20 of 25 patients (80%), posterior urethral rupture was associated with pelvic fractures and in 2 (8%), bladder rupture also was present. None of the patients had urinary incontinence. Six patients (24%) had evidence of postoperative stricture that required urethral dilatation and/or direct vision internal urethrotomy in 2 or 3 procedures under local anesthesia. Erectile dysfunction (which all responded to sildenafil) was reported by 4 patients (16%) as a decreased quality of erection. Conclusion: We believe that primary realignment of PUR is a simple procedure associated with low morbidity. It is recommended for patients who are stable and have no other significant intra-abdominal and pelvic organ injuries.